Left Main Coronary Artery Stenting in a Neonate After Arterial Switch Operation for Transposition of the Great Arteries. (January 2014) - Sinelnikov, Yuri S.; Kornilov, Igor A.; Redkin, Dmitry A.; Strelnikova, Marina S.; Ivantsov, Sergey M.; Kalinin, Roman A.; Gorbatyh, Yuri N.
Anatomical correction of transposition of the great arteries (TGA) with an intramural coronary artery is associated with high risk of coronary complications such as vessel injury and stenosis. Here, we report on a case of left main coronary artery stenting in a neonate with single coronary artery after repair for TGA.